Planting stories : the life of librarian and storyteller Pura Belpre - Denise, Anika; Escobar, Paola (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2019)
"From the author of MONSTER TRUCK and STARRING CARMEN comes a gorgeous and lyrical story about Pura Belpré, a Puerto Rican librarian who changed the world"--
Cover title.
Includes bibliographical references.
4-8.
K-3.
Keywords: Belpre, Pura -- Juvenile literature; New York Public Library -- Employees -- Biography -- Juvenile literature; Women librarians -- New York (State) -- New York -- Biography -- Juvenile literature; Authors, American -- 20th century -- Biography -- Juvenile literature; Puerto Rican women -- New York (State) -- New York -- Biography -- Juvenile literature; Women authors, Puerto Rican -- New York (State) -- New York -- Biography -- Juvenile literature; New York (N.Y.) -- Biography -- Juvenile literature; Biographies